Igneous Rock Associations 16. The Late Permian Emeishan Large Igneous Province - Shellnutt, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
The Late Permian Emeishan large igneous province (ELIP) covers ~0.3 x 106 km2 of the western margin of the Yangtze Block and Tibetan plateau of SW China with displaced, correlative units in northern Vietnam (Song Da zone). The ELIP is of particular interest because it contains numerous world-class base metal deposits and is contemporaneous with the Late Capitanian mass extinction. The flood basalts are the signature feature of the ELIP but there are also picritic and silicic volcanic rocks and layered mafic–ultramafic and silicic plutonic rocks exposed. The ELIP is divided into three zones (i.e. inner, middle and outer) which correspond to a decrease in crustal thickness from the inner to the outer zone. The eruptive age of the ELIP is ~260 Ma and is constrained by paleomagnetic observations to an interval of ≤ 3 m.y. The presence of picritic and basaltic volcanic rocks is evidence for a high temperature regime; however, it is uncertain if these magmas were derived from subcontinental lithospheric mantle or sublithospheric mantle (i.e. asthenosphere or mantle plume) sources or both. The range of Sr (ISr ≈ 0.7040 to 0.7132), Nd (εNd(T) ≈ –14 to +8), Pb (206Pb/204PbPbI ≈ 17.9 to 20.6) and Os (gOs ≈ –5 to +11) isotope values of the ultramafic and mafic rocks does not permit a conclusive answer to source origin but it is clear that some rocks were affected by crustal contamination. However, the identification of depleted isotope compositions suggests that there is a sub-lithospheric mantle component in the system. The ELIP is considered to be a mantle plume-derived large igneous province and may have contributed to ecosystem collapse during the latest Capitanian.